2011
DOI: 10.1111/j.1468-0343.2011.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and De Facto Exchange Rate Regimes

Abstract: This paper explores the relationship between a country's political regime type and its de facto exchange rate fixity. It argues that more democratic regimes should be associated with less de facto fixity because the median voter is likely to be a domestically oriented producer with a monetary preference for domestic policy autonomy, requiring more a more flexible exchange rate regime. Focusing on a broad sample of countryyears in the post-Bretton Woods era defined by international capital mobility, the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…37 We extend these selectorate-based theories of exchange rate regimes to the nondemocratic world and argue that authoritarian regimes with large selectorates should also avoid fixed exchange rates. 38 36 Bearce and hallerberg 2011;Broz 2002;frieden, ghezzi, and Stein 2001;leblang 1999;Simmons 1994; Singer 2010. one exception is frieden, leblang, and Valev's 2010 study, which found that democracies are more likely to fix their exchange rates in eastern europe. This anomalous result may be driven by the fact that most dictatorships in eastern europe are single-party regimes.…”
Section: Autocratic Regime Types and Exchange Rate Policymentioning
confidence: 98%
See 2 more Smart Citations
“…37 We extend these selectorate-based theories of exchange rate regimes to the nondemocratic world and argue that authoritarian regimes with large selectorates should also avoid fixed exchange rates. 38 36 Bearce and hallerberg 2011;Broz 2002;frieden, ghezzi, and Stein 2001;leblang 1999;Simmons 1994; Singer 2010. one exception is frieden, leblang, and Valev's 2010 study, which found that democracies are more likely to fix their exchange rates in eastern europe. This anomalous result may be driven by the fact that most dictatorships in eastern europe are single-party regimes.…”
Section: Autocratic Regime Types and Exchange Rate Policymentioning
confidence: 98%
“…This anomalous result may be driven by the fact that most dictatorships in eastern europe are single-party regimes. 37 Bearce and hallerberg 2011;eichengreen 1996, chap. 1;leblang 1999;Simmons 1994;Singer 2010, 316.…”
Section: Autocratic Regime Types and Exchange Rate Policymentioning
confidence: 98%
See 1 more Smart Citation
“…2 Theoretical arguments and empirical contributions have focused on a range of institutional measures and their connection to exchange rate regime choice. Leblang (1999) examines the role of democracy, Bearce and Hallerberg (2008) concentrate on political (in)stability, and Hall (2008) looks at the depth of democracy. All of these papers base their arguments on the logic of credible commitments and suggest that domestic political pressures can also work against the adoption of a flexible exchange rate.…”
Section: The Political Economy Of Exchange Rate Regimes: Theorymentioning
confidence: 99%
“…IPE research has shown that the costs of sacrificing domestic economic goals in order to achieve exchange rate stability are particularly high for democratically elected policymakers (e.g. Bearce & Hallerberg, 2011;Broz, 2002;M. Hall, 2008;Sattler & Walter, 2010;Simmons, 1994), but that these costs also vary substantially across different political settings.…”
Section: The Political Economy Of the Euro Crisismentioning
confidence: 99%